Preparing patients according to their individual coping style improves patient experience of magnetic resonance imaging - Madl, Janika; Sturmbauer, Sarah; Janka, Rolf Matthias; Bay, Susanne; Rohleder, Nicolas (Journal of Behavioral Medicine, 2022)
MRI-related anxiety is present in 30% of patients and may evoke motion artifacts/failed scans, which impair clinical efficiency. It is unclear how patient anxiety can be countered most effectively. Habitual preferences for coping with stressful situations by focusing or distracting one's attention thereof (coping style) may play a key role in this context. This study aimed to compare the effectiveness of two patient-preparation videos with informational vs. relaxational content and to determine whether the fit between content and coping style affects effectivity. The sample consisted of 142 patients (M = 48.31 +/- 15.81 years). Key outcomes were anxiety, and cortisol as a physiological stress marker. When not considering coping style, neither intervention improved the patients' reaction; only patient preparation that matched the patients' coping style was associated with an earlier reduction of anxiety. This suggests that considering individual preferences for patient preparation may be more effective than a one-size-fits-all approach.
CRIS-Team WoS Importer:2022-09-16